Asuhan Kebidanan Komprehensif pada Ny. R, 28 Th, G2P1A0 dengan Keputihan Fisiologis di Puskesmas Bandaran Kecamatan Tlanakan Kabupaten Pamekasan Tahun 2022 - Lianita Primi Octaviana; Raudlatul Jannah (Akademi Kebidanan Aifa Husada Madura, 2023)
Pregnancy is a normal thing to happen to a woman, which at this time involves physical and emotional changes. During pregnancy there are hormonal changes that occur in the mother, resulting in an inconvenience in the mother, for example vaginal discharge. Basically, vaginal discharge that occurs in pregnant women is a physiological thing if there is no change in color, smell and itching.. Fluor albus or commonly called vaginal discharge is a large amount of vaginal secretion with a thick or liquid contingency starting from the first trimester, but will increase more in the second trimester and III trimester, as a form of vaginal mucosal hyperplation. Although this is a physiological thing, it still makes people, especially pregnant women, feel worried. The purpose of this study was to conduct Comprehensive Obstetric Care in Mrs.R, 28 Years, G2P1A0 with Physiological Whiteness at the Puskesmas Bandaran, Tlanakan District, Pamekasan Regency. This study was conducted from January to April 2022 with a descriptive method, namely by following the patient's progress using countinue of care from pregnancy to birth control. From the results of the examination given to Mrs.